Case reportBreast cancer in pregnant women: report of two cases and review of the literature - Jakubik, Jarosław; Gottwald, Leszek; Kukulska, Monika; Góra, Ewa; Korczyński, Jerzy; Bieńkiewicz, Andrzej; Pasz-Walczak, Grażyna; Pluta, Piotr; Ciałkowska-Rysz, Aleksandra (Archives of Medical Science, 2008)
Malignant tumours in pregnant women are rare. The terms ‘gestational breast cancer (GBC)’ and ‘pregnancy-associated breast cancer’ are given to breast cancer cases diagnosed during pregnancy and up to one year post-partum. Treatment methods, as well as treatment onset and time of pregnancy termination, remain controversial. We describe two fatal cases of GBC in multiparous women over 35 years of age. The first patient was a thirty-seven year old woman with breast cancer diagnosed in the 26th week of gestation treated with surgery and postoperative chemotherapy. The second case was a thirty-nine year old pregnant woman with primary inoperable breast cancer treated with chemotherapy since the 24th week of gestation. We conclude that breast cancer during pregnancy requires a multidisciplinary approach to ensure optimal care for both the mother and the baby. Prognosis in GBC similarly to breast cancer in non-pregnant women depends mainly on the stage of the disease at the time of diagnosis.